Exploring a Figure of Speech: The Realisation of Onomatopoeia in â€œAquaman: Through Fire and Waterâ€ Webcomic - T. Thyrhaya Zein; Ihsan Tanama Sitio; Maharani, Puan (Linguistik, Terjemahan, Sastra (LINGTERSA), 2024)
The present study analyses the realisation of onomatopoeia and determines the extent of the onomatopoeic words in creating meaningful imagery, illustrating actions as well as evoking readersâ€™ sensory associations toward the storyline of a webcomic entitled â€œAquaman: Through Fire and Waterâ€. Qualitatively, this study used Krippendorffâ€™s (2018) Content Analysis (CA) as an approach. Methodologically, Miles & Hubermanâ€™s (1994) interactive qualitative data analysis was applied to analyse the data. Respectively, Bredinâ€™s (1996) framework of Onomatopoeia was also adopted to look at how the onomatopoeic words are realised. The findings showed that Direct Onomatopoeia (50%) is the most occurring type from 26 onomatopoeic words found, followed by Associative Onomatopoeia (46,15%) and Exemplary Onomatopoeia (3,84%). The realisations of the onomatopoeic words reveal that the integration of the onomatopoeic realisations with the aesthetic depiction of the images throughout the webcomic can fairly create meaningful imagery and illustrate actions of the webcomic. Thus, it evokes readersâ€™ sensory associations toward the scenes and storyline of the webcomic. Keyword: Onomatopoeia, Figure of Speech, Webcomic, Aquaman: Through Fire and Water